The Transition from Implementing the K-13 Curriculum to the Merdeka Belajar Curriculum in Elementary Schools - M. Ubaidillah Ridwanulloh; Ayu Fransiska Wulandari; Tina Nur Fitriana; Agiel Muhammad; Yulianti Yusal; Fitria Lestari (Journal of Islamic Education Students (JIES), 2024)
his research aims to describe the curriculum management implementation process at the primary school level. The phenomenon of changing times is unavoidable, especially after the COVID-19 pandemic, which has necessitated rapid changes in all aspects of human life, including education. Therefore, there has been a curriculum change in the Republic of Indonesia with the emergence of the "Merdeka Belajar " (Freedom to Learn) Curriculum as an alternative solution to address this phenomenon. The research used a qualitative method with a case study approach. Data sources were obtained through direct observation, documentation, and interviews with the school principal, Grade I, II, IV, and VI class teachers at SDN 01 Gayam Kota Kediri. This study seeks to uncover the curriculum transition process from the K-13 curriculum to the "Merdeka Belajar " curriculum in primary education units. The research findings indicate that the implementation of the "Merdeka Belajar " curriculum management is going well. The process includes planning and preparation through training and workshops, implementing learning based on the "Merdeka Belajar " curriculum, and continuous evaluation of the achievement of learning outcomes (CP). The "Merdeka Belajar " Curriculum Management process is effective and efficient.